Authigenic ultrahigh-temperature ceramic reinforced silicon carbide composite material and preparation method thereof
By using raw materials such as polycarbosilane, ultra-high temperature metal oligomers, combined with pioneer crosslinking and high temperature sintering, a self-generated ultra-high temperature ceramic reinforced silicon carbide composite was prepared, which solved the problem of degradation of mechanical properties of SiC ceramic composites at high temperatures, and achieved the preparation of high strength, high temperature resistance and complex shapes.
Patent Information
- Application Number
- CN202311434409.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-31
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2043-10-31
AI Technical Summary
The existing SiC ceramic composite materials have grain coarsing and amorphous phase decomposition at high temperatures, resulting in a decrease in mechanical properties, and it is difficult to achieve three-dimensional molding and high ceramic yields.
Polycarbosilane, ultra-high temperature metal oligomer, graphene oxide, silane coupling agent and boron powder are used as raw materials to prepare self-generated ultra-high temperature ceramic reinforced silicon carbide composite materials through pioneer cross-linking, high-temperature cracking, ball mill blending, molding and high-temperature sintering.
It realizes low density, high mechanical strength, high temperature resistance, oxidation resistance and complex shape preparation, improving the comprehensive performance of ceramics and the feasibility of industrial production.
Smart Images

Figure CN119569461A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of ceramic materials, and in particular to a self-generated ultra-high temperature ceramic reinforced silicon carbide composite material and a preparation method thereof. Background Art
[0002] Silicon carbide (SiC) composites have unique properties such as excellent mechanical properties, high temperature resistance, oxidation resistance, thermal shock resistance and good chemical stability, making them the first choice for manufacturing high-performance aerospace hot end components, such as continuous fiber reinforced ceramic matrix composites C f / SiC、SiC f / SiC. SiC ceramic composite materials can usually be obtained by preparation methods such as normal pressure sintering, hot pressing sintering and reaction sintering, but they have strong covalent bonds and a high melting point, so the sintering processability is poor, the sintering temperature is high, the density is low, and additives are usually required, which affects the overall performance of the product.
[0003] The precursor conversion method has become a research hotspot for the preparation of SiC ceramic composite structural materials due to its unique advantages such as molecular structure designability, controllable composition and high purity, good machinability, low sintering temperature, and no need to add sintering aids. However, traditional ceramic precursors will produce a large amount of thermal stress and small molecule gases during cracking, resulting in a large number of defects and holes, severe volume shrinkage, and poor fracture toughness, which is not conducive to the stable molding of the ceramic matrix and is often made into low-dimensional materials such as fibers. Chinese patent ZL201910826944.7 discloses a blending and re-cracking method using graphene oxide-vinyltriethoxysilane-polycarbosilane precursors. The prepared SiC composite structural block ceramic has a high ceramic yield and low shrinkage rate, but the high temperature resistance and mechanical properties of the ceramic need to be improved.
[0004] As composite materials for hot-end components of aerospace are developing towards light weight, high strength, ultra-high temperature resistance and structural and functional integration, higher requirements are put forward for SiC composite materials obtained by precursor conversion method. SiC grains in the structure of SiC composite materials by precursor conversion method are produced by the decomposition of silicon oxygen carbon (SiOxCy) amorphous phase. Usually, the grains will begin to grow when the temperature is greater than 1200℃. At higher temperatures, SiC grains will coarsen and the amorphous phase will further decompose to form holes, which will lead to a sharp decline in mechanical properties. In order to control production costs and industrial large-scale applications, the introduction of ultra-high temperature metal elements is currently mainly used to inhibit grain growth, while strengthening SiC ceramics and improving high temperature resistance. Chinese patent ZL 200710034593.3 discloses a method and device for preparing a zirconium-containing polycarbosilane ceramic precursor, using silicon-containing polymers and zirconium-containing organic metal compounds as raw materials, preparing SiC ceramic precursor polyzirconium carbosilane (PZCS) containing heterogeneous zirconium by atmospheric high temperature pyrolysis to prepare zirconium-containing ultra-high temperature resistant ceramics. Chinese patent ZL 200710192459.6 discloses a method for synthesizing a tantalum-containing SiC ceramic precursor, wherein a low molecular weight polymer tantalum metal organic compound or chloride containing silicon in the main chain is subjected to a cracking and rearrangement reaction to obtain a tantalum-containing SiC ceramic precursor polytantalum carbon silane (PTCS), which is used to prepare ceramic fibers with excellent antioxidant properties. Chinese patent ZL201710913312.5 discloses a method for preparing a zirconium-containing ceramic precursor, wherein SiC-ZrC-ZrO is obtained by a coordination chelation reaction of zirconium n-propoxide and acetylacetone, a substitution reaction of the chelation product with ethylene glycol, centrifugation, and solvent removal. 2 Composite ceramic precursor, used in high temperature resistant materials. Chinese patent ZL 202211523584.1 discloses a method for preparing a polymetallic carbosilane precursor, using alkali metal, metallocene and chlorosilane as raw materials to obtain polymetallic carbosilane with a high metal content. Chinese patent ZL201910720382.8 discloses a method for preparing a polymetallic carbosilane precursor containing nano ZrB 2 -Hf SiC fiber and its preparation method and application, using polyacetylacetonate zirconium, boric acid, phenolic resin as raw materials to prepare hydrogel and then drying to obtain powder, then mixing metal hafnium to perform high temperature cracking and ball milling to obtain ZrB 2 -Hf nano powder, then add polycarbosilane powder and use supercritical fluid recrystallization method to melt spin to prepare fibers, and then treat the cross-linked fibers without melting and finally sinter to obtain nano ZrB 2-Hf SiC fiber. However, the ceramic precursors synthesized by these methods are difficult to achieve three-dimensional molding and are limited to low-dimensional ceramic fibers. At the same time, silicon-containing polymers are prone to curling and winding, and the exposed active reaction sites are limited. The content of heterogeneous elements that coordinate with Si to form chemical bonds in the precursor is low, and most of them are mechanically blended. The oxygen-rich organic groups in ultra-high temperature metal compounds, such as acetylacetone, isopropanol, and hydroxyl groups, are beneficial to improving their solubility and reactivity, but the presence of organic groups cannot be completely removed, resulting in a high oxygen content in the ceramic precursor, which affects the high temperature resistance. Using low molecular weight silane and ultra-high temperature oxygen-free metal small molecule compounds as raw materials, such as a new method for preparing zirconium-containing polycarbosilane disclosed in Chinese patent ZL202110987521.0, zirconium chloride and chlorine-containing polysilane undergo Grignard reaction to obtain zirconium-containing polysilane, which is then cracked and rearranged at high temperature and normal pressure. It is inevitable to use low-boiling tetrahydrofuran solvents, which require desalination and the reaction conditions are difficult to control, making it difficult to achieve industrial production. Summary of the invention
[0005] The purpose of the present invention is to solve the above problems in the prior art and provide a self-generated ultra-high temperature ceramic reinforced silicon carbide composite material with low density, high mechanical strength, high temperature resistance, oxidation resistance, and the ability to make complex shapes. Another purpose of the present invention is to provide a simple and economical preparation method of the above SiC composite material suitable for industrial production.
[0006] The self-generated ultra-high temperature ceramic reinforced silicon carbide composite material is prepared from polycarbosilane, ultra-high temperature metal oligomers, graphene oxide, silane coupling agent, polymer precursor polycarbosilane-graphene oxide (PVG) and boron powder as raw materials, and adopts processes such as precursor crosslinking, high temperature cracking, ball milling blending, molding, and high temperature sintering.
[0007] In order to achieve the above object, the present invention adopts the following technical scheme:
[0008] A method for preparing an in-situ ultra-high temperature ceramic reinforced silicon carbide composite material comprises the following steps:
[0009] 1) dissolving polycarbosilane powder and ultra-high temperature metal oligomer powder in an organic solvent by ultrasonic dispersion, and then placing under a protective atmosphere to undergo high temperature reflux, distillation and high temperature crosslinking to obtain a solid, grinding to obtain a powder, dissolving the powder in an organic solvent to obtain a modified polycarbosilane solution, and dropping a platinum catalyst; adding a silane coupling agent to a graphene oxide dispersion, mixing the mixture into the modified polycarbosilane solution to which the platinum catalyst has been dropped, heating in a water bath with stirring for reaction, rotary evaporation and grinding to obtain a SiC ceramic precursor powder;
[0010] 2) PVG powder and ultra-high temperature metal oligomer powder are uniformly dispersed and mixed in an organic solvent by ultrasonic dispersion, and then placed in a protective atmosphere for high temperature reflux, distillation and high temperature cross-linking, and then cooled, taken out, ground, and finally placed in a tube furnace for high temperature cracking to obtain SiC ceramic filler powder;
[0011] 3) The SiC ceramic precursor powder prepared in step 1), the SiC ceramic filler powder prepared in step 2) and the boron powder are mixed evenly in a planetary ball mill, and the abrasive is fully dried to obtain a mixed powder, which is poured into a mold for tableting, and demolded to obtain a ceramic green body, which is then placed in a tubular furnace for high-temperature sintering under protective atmosphere to obtain a self-generated ultra-high temperature ceramic reinforced silicon carbide composite material.
[0012] In step 1) and step 2), the preparation method of the ultra-high temperature metal oligomer powder is to subject one or more of diisopropyl di(acetylacetonate) titanate, acetylacetonoxy titanium, acetylacetonate zirconium, acetylacetonate hafnium, acetylacetonate aluminum, acetylacetonate tantalum, acetylacetonate yttrium, acetylacetonate chromium, and acetylacetonate nickel to a self-polymerization reaction in a constant temperature oil bath at 160 to 200° C. for 0.5 to 3 hours to obtain the powder, with a yield of 40% to 75%.
[0013] In step 1) and step 2), the organic solvent is xylene, and the protective atmosphere is one of argon and nitrogen.
[0014] In step 1), the mass ratio of polycarbosilane powder to ultra-high temperature metal oligomer powder is 100:(5-100), the reaction conditions are reflux at 140-160°C for 2-6 hours, then heating to distill the solvent, and cross-linking reaction at 290-310°C for 2-4 hours; the concentration of the modified polycarbosilane solution is 0.01-0.1 g / mL.
[0015] In step 1), the water bath heating and stirring is at 50°C to 70°C and a rotation speed of 5 to 20 rpm for 20 to 60 min.
[0016] In step 2), the mass ratio of PVG powder to ultrahigh temperature metal oligomer powder is 100:(10-200), the reaction conditions are reflux at 140-160° C. for 2-6 hours, then heating to distill the solvent, and cross-linking reaction at 290-310° C. for 2-4 hours.
[0017] In step 2), the high temperature pyrolysis is placed in an argon atmosphere (flow rate 50-100 mL·min -1 ) at 3~10℃·min -1 The temperature is raised to 900-1500°C at a heating rate and kept at this temperature for 1-60 minutes.
[0018] In step 3), the mass ratio of SiC ceramic precursor powder, SiC ceramic filler powder and boron powder is 100:(0-200):(0-23).
[0019] In step 3), the ball milling time is 9 to 20 hours, the rotation speed is 300 to 400 rpm; the tableting pressure is 90 to 300 MPa, and the holding time is 15 to 30 seconds.
[0020] In step 3), the high temperature sintering is placed in an argon atmosphere (flow rate 50-100 mL·min -1 ) at 3~10℃·min -1 The temperature is raised to 900-1500°C at a heating rate and kept at this temperature for 1-60 minutes.
[0021] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:
[0022] 1. The self-generated ultra-high temperature ceramic reinforced silicon carbide composite material prepared by the present invention is uniform, dense and crack-free, and has the advantages of low density, high strength, high hardness, ultra-high temperature resistance and oxidation resistance. The in-situ self-generated ultra-high temperature ceramic nanostructured particles can adaptively and fully improve the interface compatibility, thereby effectively enhancing the SiC matrix and improving the comprehensive performance of the composite material, which is of great significance for its application in complex and harsh environments such as aerospace vehicle structural parts.
[0023] 2. The self-generated ultra-high temperature ceramic reinforced silicon carbide composite material prepared by the present invention has good three-dimensional formability, uniform microscopic composition and compact structure. The ultra-high temperature metal oligomers are connected to the SiC ceramic precursor by the precursor method, and the ultra-high temperature elements are fully introduced. During high-temperature sintering, the in-situ self-generated ultra-high temperature nanostructured ceramics (carbides, borides, oxides) are uniformly embedded in the β-SiC / SiOxCy / C free In the system, the interfaces of each phase are closely connected, and the ultra-high temperature ceramic grains and β-SiC grains inhibit each other's growth, achieving fine grain strengthening, increasing the disorder degree of the ceramic amorphous phase, and helping to improve its mechanical properties and high temperature resistance. At the same time, it also solves the bottleneck problem that carbides, borides, and oxides cannot be used alone in high temperature corrosion environments, that is, self-generated ultra-high temperature ceramic reinforced silicon carbide composites are easy to generate dense glass composite oxide layers under high temperature oxidation, and ultra-high temperature metal oxides improve the single SiO 2 The anti-oxidation temperature of the oxide layer prevents oxygen from further diffusing into the interior of the composite material, greatly improving the ultra-high temperature resistance and anti-oxidation performance.
[0024] 3. The self-generated ultra-high temperature ceramic reinforced silicon carbide composite material prepared by the present invention has a high content of ultra-high temperature ceramics and is evenly distributed, which solves the problem of limited introduction of ultra-high temperature elements and avoids the problem of excessive oxygen content in ceramics. The cross-linking degree of the precursor is effectively improved to ensure the high ceramic yield of the composite material, and improves the three-dimensional forming ability of the ceramic without introducing a sintering aid. This is due to the fact that the structure of the ultra-high temperature metal oligomer is an acetylacetone ultra-high temperature metal cyclic self-polymer (n≈3), and part of the acetylacetone group is removed during polymerization to avoid the organic group from being completely removed during the cross-linking process of the ceramic precursor, resulting in a high oxygen content in the product that affects the high temperature resistance, but a part of the organic group is still retained to ensure solubility and reactivity. Compared with the acetylacetone ultra-high temperature metal monomer, the ratio of ultra-high temperature metal elements / acetylacetone groups is greatly improved, and the consumption of the same amount of Si-H can coordinate more ultra-high temperature metal elements, which solves the problem of limited content of heterogeneous elements introduced into the traditional SiC precursor by chemical coordination. The use of PVG and ultra-high temperature metal oligomer cross-linking can further increase the coordination access content of ultra-high temperature metal elements. This is because the mesh graphene in the PVG structure disperses the polycarbosilane, which can prevent it from curling and winding during cross-linking, giving full play to the cross-linking effect of the Si-H active reaction sites on the polycarbosilane, bonding more ultra-high temperature metal elements, greatly increasing the molecular weight of the precursor, and can improve the ceramic yield, high temperature stability, fracture toughness, hardness, strength, etc. of SiC composite materials, and eliminate cracks in the composite material. In addition, the boron powder active filler is uniformly introduced during ball milling, which can react with oxygen, free carbon and ultra-high temperature oxides in the ceramic system during high temperature sintering to generate B 2 O 3 , B 4 C and ultra-high temperature boride phase, molten B 2 O 3 Can improve sample density, B 2 O 3 Partial volatilization reduces the oxygen content of the system and improves high temperature resistance. 4 C consolidates free carbon and improves oxidation resistance, and the ultra-high temperature boride phase generated by the thermal reaction of boron is beneficial to improving the mechanical properties and thermal shock resistance of SiC composites.
[0025] 4. The in-situ ultra-high temperature ceramic reinforced silicon carbide composite material preparation process proposed in the present invention is simple and economical, the conditions are easy to control, and it is easy to promote to achieve industrial production. In particular, in terms of ceramic yield, linear shrinkage, porosity, density, hardness, fracture toughness, mechanical strength and other functional properties, it can be regulated by adjusting the element type and addition amount in the ultra-high temperature metal oligomer, the ultra-high temperature metal content in the precursor powder or ceramic filler powder, the precursor powder / ceramic filler powder / boron powder ratio and other technical parameters. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1X-ray diffraction patterns of the self-generated ultra-high temperature ceramic reinforced silicon carbide composite materials of Example 4 and Example 5.
[0027] Figure 2 This is the infrared spectrum of the gray-brown precursor powder described in Examples 1 to 3.
[0028] Figure 3 It is the infrared spectra of the brown solid powder of PVG, poly(zirconium titanium aluminum acetylacetonate), poly(zirconium acetylacetonate) and the ceramic filler precursor of Examples 3 to 7.
[0029] Figure 4 This is a scanning electron microscope image of the surface of the self-generated ultra-high temperature ceramic reinforced silicon carbide composite material of Example 1; Figure 4 In the figure, (a) corresponds to a low-magnification surface scanning electron microscope image, and (b) corresponds to a high-magnification surface scanning electron microscope image.
[0030] Figure 5 This is a scanning electron microscope image of the surface of the self-generated ultra-high temperature ceramic reinforced silicon carbide composite material of Example 6; Figure 5 In the figure, (a) corresponds to a low-magnification surface scanning electron microscope image, and (b) corresponds to a high-magnification surface scanning electron microscope image. DETAILED DESCRIPTION
[0031] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention clearer and more understandable, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments.
[0032] Example 1
[0033] 1) 1.08 g of zirconium acetylacetonate was placed in a 250 mL three-necked flask, argon was introduced, and the mixture was reacted in an oil bath at 190° C. for 2 h. The mixture was cooled, taken out and ground to obtain orange-red zirconium polyacetylacetonate powder.
[0034] 2) 4 g of polycarbosilane powder and the polyacetylacetonate zirconium powder obtained in step 1) were mixed and added with 40 mL of xylene and then ultrasonically dispersed for 30 min to obtain an orange-red solution. The solution was then poured into a two-necked flask, a distillation device and a reflux device were set up, and argon gas was passed through. After reacting at 150° C. for 3 h, the temperature was raised to 160° C. to evaporate the xylene, and cross-linked at 300° C. for 3 h to obtain an orange solid, which was ground to obtain an orange powder.
[0035] 3) Take 2g of the orange powder prepared in step 2) and add it to 40mL of xylene to dissolve to obtain an orange solution, and then add 0.05mL of Custer platinum catalyst. Add 0.02g of GO powder to 40mL of distilled water and disperse it evenly by ultrasonication, then add 2mL of vinyltriethoxysilane, and adjust the pH of the solution to below 2 with dilute hydrochloric acid. Mix the above two solutions in a beaker, stir the reaction in a water bath at 60℃ for 30min, and then let it stand for 30min. Take the upper brown-gray organic layer, rotary evaporate it under vacuum at 70℃ for 40min, and grind it to obtain a gray-brown precursor powder.
[0036] 4) The gray-brown precursor powder obtained in step 3) is poured into a circular stainless steel mold with a diameter of 16 mm, and the mold is demolded after maintaining the pressure at 100 MPa on a hydraulic press for 20 seconds to obtain a ceramic green body.
[0037] 5) The ceramic green body obtained in step 4) was placed in a tube furnace under the protection of argon atmosphere (flow rate 60 mL·min -1 ) and then sintered again at 1300℃ (heating rate 4℃·min -1 ), keep warm for 30 minutes and then cool with the furnace to obtain a black self-generated ultra-high temperature ceramic reinforced silicon carbide composite material.
[0038] Basic physical parameters: The ceramic yield of the silicon carbide composite material is 80.75% to 81.60%, the linear shrinkage is 25% to 26.5%, and the density is 1.99 to 2.15 g / cm 3 , the open pore volume fraction is 15.16% to 16.23%.
[0039] Mechanical properties test: The hardness of the silicon carbide composite material is 11.51~12.98GPa, and the fracture toughness is 2.24~3.80MPa·m 1 / 2 .
[0040] Example 2
[0041] 1) 4.32 g of zirconium acetylacetonate was placed in a 250 mL three-necked flask, argon was introduced, and the mixture was reacted in an oil bath at 190° C. for 2 h. The mixture was cooled, taken out and ground to obtain orange-red zirconium polyacetylacetonate powder.
[0042] 2) 4 g of polycarbosilane powder and the polyacetylacetonate zirconium powder obtained in step 1) were mixed and added with 40 mL of xylene and then ultrasonically dispersed for 30 min to obtain an orange-red solution. The solution was then poured into a two-necked flask, a distillation device and a reflux device were set up, and argon gas was passed through. After reacting at 150° C. for 3 h, the temperature was raised to 160° C. to evaporate the xylene, and cross-linked at 300° C. for 3 h to obtain an orange solid, which was ground to obtain an orange powder.
[0043] 3) Take 2g of the orange powder prepared in step 2) and add it to 40mL of xylene to dissolve to obtain an orange solution, and then add 0.05mL of Custer platinum catalyst. Add 0.02g of GO powder to 40mL of distilled water and disperse it evenly by ultrasonication, then add 2mL of vinyltriethoxysilane, and adjust the pH of the solution to below 2 with dilute hydrochloric acid. Mix the above two solutions in a beaker, stir the reaction in a water bath at 60℃ for 30min, and then let it stand for 30min. Take the upper brown-gray organic layer, rotary evaporate it under vacuum at 70℃ for 40min, and grind it to obtain a gray-brown precursor powder.
[0044] 4) The gray-brown precursor powder obtained in step 3) is poured into a circular stainless steel mold with a diameter of 16 mm, and the mold is demolded after maintaining the pressure at 100 MPa on a hydraulic press for 20 seconds to obtain a ceramic green body.
[0045] 5) The ceramic green body obtained in step 4) was placed in a tube furnace under the protection of argon atmosphere (flow rate 60 mL·min -1 ) and then sintered again at 1300℃ (heating rate 4℃·min -1 ), keep warm for 30 minutes and then cool with the furnace to obtain a black self-generated ultra-high temperature ceramic reinforced silicon carbide composite material.
[0046] Basic physical parameters: The ceramic yield of the silicon carbide composite material is 77.23% to 78.10%, the linear shrinkage is 21.80% to 23.65%, and the density is 1.82 to 1.99 g / cm 3 , the open pore volume fraction is 21.86% to 22.95%.
[0047] Mechanical properties test: The hardness of the silicon carbide composite material is 4.63~7.16GPa, and the fracture toughness is 1.71~3.01MPa·m 1 / 2 .
[0048] Example 3
[0049] 1) 2.16 g of zirconium acetylacetonate was placed in a 250 mL three-necked flask, argon was introduced, and the mixture was reacted in an oil bath at 190° C. for 2 h. The mixture was cooled, taken out and ground to obtain orange-red zirconium polyacetylacetonate powder.
[0050] 2) 4 g of polycarbosilane powder and the polyacetylacetonate zirconium powder obtained in step 1) were mixed and added with 40 mL of xylene and then ultrasonically dispersed for 30 min to obtain an orange-red solution. The solution was then poured into a two-necked flask, a distillation device and a reflux device were set up, and argon gas was passed through. After reacting at 150° C. for 3 h, the temperature was raised to 160° C. to evaporate the xylene, and cross-linked at 300° C. for 3 h to obtain an orange solid, which was ground to obtain an orange powder.
[0051] 3) Take 2g of the orange powder prepared in step 2) and add it to 40mL of xylene to dissolve to obtain an orange solution, and then add 0.05mL of Custer platinum catalyst. Add 0.02g of GO powder to 40mL of distilled water and disperse it evenly by ultrasonication, then add 2mL of vinyltriethoxysilane, and adjust the pH of the solution to below 2 with dilute hydrochloric acid. Mix the above two solutions in a beaker, stir the reaction in a water bath at 60℃ for 30min, and then let it stand for 30min. Take the upper brown-gray organic layer, rotary evaporate it under vacuum at 70℃ for 40min, and grind it to obtain a gray-brown precursor powder.
[0052] 4) Add 2g of polycarbosilane powder to 40mL of xylene to dissolve to obtain a transparent colorless solution, and then add 0.05mL of Custer platinum catalyst to obtain a golden solution. Add 0.02g of GO powder to 40mL of distilled water, ultrasonically disperse it evenly, then add 2mL of vinyltriethoxysilane, and adjust the pH of the solution to below 2 with dilute hydrochloric acid. Mix the above two solutions in a beaker, stir magnetically in a 60℃ water bath to react for 30min. After the reaction is completed, take out the beaker and let it stand for 30min. Take the upper gray organic layer and rotary evaporate it under vacuum at 70℃ for 40min, then grind it to obtain a gray solid powder PVG.
[0053] 5) 6.48 g of zirconium acetylacetonate was placed in a 250 mL three-necked flask, argon was introduced, and the mixture was reacted in an oil bath at 190° C. for 2 h. The mixture was cooled, taken out and ground to obtain orange-red zirconium polyacetylacetonate powder.
[0054] 6) 4 g of the PVG powder described in step 4) and the polyacetylacetonate zirconium powder described in step 5) were mixed and added to 40 mL of xylene and then ultrasonically dispersed for 30 min to obtain a reddish brown turbid liquid. Then the mixture was poured into a two-necked flask, a distillation device and a reflux device were set up, and argon gas was passed through. After reacting at 150° C. for 3 h, the temperature was raised to 160° C. to evaporate the xylene, and then reacted at 300° C. for 3 h and ground to obtain a brown solid powder of a ceramic filler precursor.
[0055] 7) The brown solid powder obtained in step 6) was placed in an alumina crucible and heated in an argon atmosphere (flow rate 60 mL min -1 ) was pyrolyzed at 1300℃ in a tube furnace (heating rate 4℃·min -1 ), keep warm for 30 minutes and then cool with the furnace to obtain black self-generated ultra-high temperature ceramic reinforced SiC ceramic filler powder.
[0056] 8) The gray-brown precursor powder obtained in step 3) and the self-generated ultra-high temperature ceramic reinforced SiC ceramic filler powder obtained in step 7) are mixed uniformly in a mass ratio of 1:1 using a planetary ball mill. The ball milling adopts a forward and reverse alternating mode, and the rotation direction is changed every 1 hour. The mass ratio of the abrasive and the grinding ball is 1:4, the medium is anhydrous ethanol, the rotation speed is 400 rpm, and the ball milling time is 18 hours. After ball milling, the abrasive is fully dried to obtain a black mixed powder.
[0057] 9) 0.5 g of the black mixed powder obtained in step 8) was poured into a 16 mm diameter round stainless steel mold, and the mold was demolded after maintaining the pressure at 200 MPa on a hydraulic press for 20 seconds to obtain a ceramic green body.
[0058] 10) The ceramic green body obtained in step 9) was placed in a tube furnace under the protection of argon atmosphere (flow rate 60 mL min -1 ) and then sintered again at 1300℃ (heating rate 4℃·min -1 ), keep warm for 30 minutes and then cool with the furnace to obtain a black self-generated ultra-high temperature ceramic reinforced silicon carbide composite material.
[0059] Basic physical parameters: The ceramic yield of the silicon carbide composite material is 89.85-91.20%, the linear shrinkage is 9.25-10.13%, and the density is 1.72-1.79 g / cm 3 , the open pore volume fraction is 29.12~30.64%.
[0060] Mechanical properties test: The hardness of the silicon carbide composite material is 3.06~5.05GPa, and the fracture toughness is 2.24~3.05MPa·m 1 / 2 The bending strength is 50.46~62.11MPa, and the compressive strength is 245.16~265.77MPa.
[0061] Example 4
[0062] 1) 0.950 g of zirconium acetylacetonate, 0.108 g of titanium acetylacetonate and 0.024 g of aluminum acetylacetonate were placed in a 250 mL three-necked flask, argon was introduced, and the mixture was reacted in an oil bath at 190° C. for 75 min, then cooled, taken out and ground to obtain polyzirconium titanium aluminum acetylacetonate orange-red powder.
[0063] 2) Take 4g of polycarbosilane powder and the polyacetylacetonate zirconium titanium aluminum powder obtained in step 1), mix them, add 40mL of xylene, and then ultrasonically disperse for 30 minutes to obtain an orange-red solution. Then pour the solution into a two-necked flask, set up a distillation device and a reflux device, and pass argon protection. After reacting at 150°C for 3h, heat it to 160°C to evaporate the xylene, crosslink at 300°C for 3h to obtain an orange solid, and grind it to obtain an orange powder.
[0064] 3) Take 2g of the orange powder prepared in step 2) and add it to 40mL of xylene to dissolve to obtain an orange solution, and then add 0.05mL of Custer platinum catalyst. Add 0.02g of GO powder to 40mL of distilled water and disperse it evenly by ultrasonication, then add 2mL of vinyltriethoxysilane, and adjust the pH of the solution to below 2 with dilute hydrochloric acid. Mix the above two solutions in a beaker, stir the reaction in a water bath at 60℃ for 30min, and then let it stand for 30min. Take the upper brown-gray organic layer, rotary evaporate it under vacuum at 70℃ for 40min, and grind it to obtain a gray-brown precursor powder.
[0065] 4) Add 2g of polycarbosilane powder to 40mL of xylene to dissolve to obtain a transparent colorless solution, and then add 0.05mL of Custer platinum catalyst to obtain a golden solution. Add 0.02g of GO powder to 40mL of distilled water, ultrasonically disperse it evenly, then add 2mL of vinyltriethoxysilane, and adjust the pH of the solution to below 2 with dilute hydrochloric acid. Mix the above two solutions in a beaker, stir magnetically in a 60℃ water bath to react for 30min. After the reaction is completed, take out the beaker and let it stand for 30min. Take the upper gray organic layer and rotary evaporate it under vacuum at 70℃ for 40min, then grind it to obtain a gray solid powder PVG.
[0066] 5) 2.851 g of zirconium acetylacetonate, 0.324 g of titanium acetylacetonate and 0.072 g of aluminum acetylacetonate were placed in a 250 mL three-necked flask, argon was introduced, and the mixture was reacted in an oil bath at 190° C. for 75 min, then cooled, taken out and ground to obtain polyzirconium titanium aluminum acetylacetonate orange-red powder.
[0067] 6) 4 g of the PVG powder described in step 4) and the polyacetylacetonate zirconium titanium aluminum powder described in step 5) were mixed and added to 40 mL of xylene and then ultrasonically dispersed for 30 min to obtain a reddish brown turbid liquid. Then the mixture was poured into a two-necked flask, a distillation device and a reflux device were set up, and argon gas was passed through. After reacting at 150° C. for 3 h, the temperature was raised to 160° C. to evaporate the xylene, and then reacted at 300° C. for 3 h and ground to obtain a brown solid powder of a ceramic filler precursor.
[0068] 7) The brown solid powder obtained in step 6) was placed in an alumina crucible and heated in an argon atmosphere (flow rate 60 mL min -1 ) was pyrolyzed at 1300℃ in a tube furnace (heating rate 4℃·min -1 ), keep warm for 30 minutes and then cool with the furnace to obtain black self-generated ultra-high temperature ceramic reinforced SiC ceramic filler powder.
[0069] 8) The gray-brown precursor powder obtained in step 3) and the self-generated ultra-high temperature ceramic reinforced SiC ceramic filler powder obtained in step 7) are mixed uniformly in a mass ratio of 1:1 using a planetary ball mill. The ball milling adopts a forward and reverse alternating mode, and the rotation direction is changed every 1 hour. The mass ratio of the abrasive and the grinding ball is 1:4, the medium is anhydrous ethanol, the rotation speed is 400 rpm, and the ball milling time is 18 hours. After ball milling, the abrasive is fully dried to obtain a black mixed powder.
[0070] 9) 0.5 g of the black mixed powder obtained in step 8) was poured into a 16 mm diameter round stainless steel mold, and the mold was demolded after maintaining the pressure at 200 MPa on a hydraulic press for 20 seconds to obtain a ceramic green body.
[0071] 10) The ceramic green body obtained in step 9) was placed in a tube furnace under the protection of argon atmosphere (flow rate 60 mL min -1 ) and then sintered again at 1300℃ (heating rate 4℃·min -1 ), keep warm for 30 minutes and then cool with the furnace to obtain a black self-generated ultra-high temperature ceramic reinforced silicon carbide composite material.
[0072] Basic physical parameters: The ceramic yield of the silicon carbide composite material is 91.60-91.70%, the linear shrinkage is 7.88-8.43%, and the density is 1.59-1.68 g / cm 3 , the open pore volume fraction is 28.13~33.28%.
[0073] Mechanical properties test: The hardness of the silicon carbide composite material is 3.06-5.05GPa, and the fracture toughness is 3.65-4.23MPa·m 1 / 2 The bending strength is 44.89~60.28MPa, and the compressive strength is 222.63~243.74MPa.
[0074] Example 5
[0075] 1) 0.950 g of zirconium acetylacetonate, 0.108 g of titanium acetylacetonate and 0.024 g of aluminum acetylacetonate were placed in a 250 mL three-necked flask, argon was introduced, and the mixture was reacted in an oil bath at 190° C. for 75 min, then cooled, taken out and ground to obtain polyzirconium titanium aluminum acetylacetonate orange-red powder.
[0076] 2) Take 4g of polycarbosilane powder and the polyacetylacetonate zirconium titanium aluminum powder obtained in step 1), mix them, add 40mL of xylene, and then ultrasonically disperse for 30 minutes to obtain an orange-red solution. Then pour the solution into a two-necked flask, set up a distillation device and a reflux device, and pass argon protection. After reacting at 150°C for 3h, heat it to 160°C to evaporate the xylene, crosslink at 300°C for 3h to obtain an orange solid, and grind it to obtain an orange powder.
[0077] 3) Take 2g of the orange powder prepared in step 2) and add it to 40mL of xylene to dissolve to obtain an orange solution, and then add 0.05mL of Custer platinum catalyst. Add 0.02g of GO powder to 40mL of distilled water and disperse it evenly by ultrasonication, then add 2mL of vinyltriethoxysilane, and adjust the pH of the solution to below 2 with dilute hydrochloric acid. Mix the above two solutions in a beaker, stir the reaction in a water bath at 60℃ for 30min, and then let it stand for 30min. Take the upper brown-gray organic layer, rotary evaporate it under vacuum at 70℃ for 40min, and grind it to obtain a gray-brown precursor powder.
[0078] 4) Add 2g of polycarbosilane powder to 40mL of xylene to dissolve to obtain a transparent colorless solution, and then add 0.05mL of Custer platinum catalyst to obtain a golden solution. Add 0.02g of GO powder to 40mL of distilled water, ultrasonically disperse it evenly, then add 2mL of vinyltriethoxysilane, and adjust the pH of the solution to below 2 with dilute hydrochloric acid. Mix the above two solutions in a beaker, stir magnetically in a 60℃ water bath to react for 30min. After the reaction is completed, take out the beaker and let it stand for 30min. Take the upper gray organic layer and rotary evaporate it under vacuum at 70℃ for 40min, then grind it to obtain a gray solid powder PVG.
[0079] 5) 2.851 g of zirconium acetylacetonate, 0.324 g of titanium acetylacetonate and 0.072 g of aluminum acetylacetonate were placed in a 250 mL three-necked flask, argon was introduced, and the mixture was reacted in an oil bath at 190° C. for 75 min, then cooled, taken out and ground to obtain polyzirconium titanium aluminum acetylacetonate orange-red powder.
[0080] 6) 4 g of the PVG powder described in step 4) and the polyacetylacetonate zirconium titanium aluminum powder described in step 5) were mixed and added to 40 mL of xylene and then ultrasonically dispersed for 30 min to obtain a reddish brown turbid liquid. Then the mixture was poured into a two-necked flask, a distillation device and a reflux device were set up, and argon gas was passed through. After reacting at 150° C. for 3 h, the temperature was raised to 160° C. to evaporate the xylene, and then reacted at 300° C. for 3 h and ground to obtain a brown solid powder of a ceramic filler precursor.
[0081] 7) The brown solid powder obtained in step 6) was placed in an alumina crucible and heated in an argon atmosphere (flow rate 60 mL min -1 ) was pyrolyzed at 1300℃ in a tube furnace (heating rate 4℃·min -1 ), keep warm for 30 minutes and then cool with the furnace to obtain black self-generated ultra-high temperature ceramic reinforced SiC ceramic filler powder.
[0082] 8) The gray-brown precursor powder obtained in step 3), the self-generated ultra-high temperature ceramic reinforced SiC ceramic filler powder obtained in step 7) and the boron powder are uniformly mixed in a planetary ball mill at a mass ratio of 100:100:5.5, and the ball milling adopts a positive and reverse alternating mode, and the rotation direction is changed every 1 hour. The mass ratio of the abrasive and the grinding ball is 1:4, the medium is anhydrous ethanol, the rotation speed is 400 rpm, and the ball milling time is 18 hours. After ball milling, the abrasive is fully dried to obtain a black mixed powder.
[0083] 9) 0.5 g of the black mixed powder obtained in step 8) was poured into a 16 mm diameter round stainless steel mold, and the mold was demolded after maintaining the pressure at 200 MPa on a hydraulic press for 20 seconds to obtain a ceramic green body.
[0084] 10) The ceramic green body obtained in step 9) was placed in a tube furnace under the protection of argon atmosphere (flow rate 60 mL min -1 ) and then sintered again at 1300℃ (heating rate 4℃·min -1 ), keep warm for 30 minutes and then cool with the furnace to obtain a black self-generated ultra-high temperature ceramic reinforced silicon carbide composite material.
[0085] Basic physical parameters: The ceramic yield of silicon carbide composite material is 91.60-92.32%, the linear shrinkage is 8.00-8.50%, and the density is 1.60-1.72 g / cm 3 , the open pore volume fraction is 27.85~32.59%.
[0086] Mechanical properties test: The hardness of the silicon carbide composite material is 7.74-8.75GPa, and the fracture toughness is 3.95-4.57MPa·m 1 / 2 The bending strength is 49.45~63.74MPa, and the compressive strength is 230.80~257.90MPa.
[0087] Example 6
[0088] 1) 2.16 g of zirconium acetylacetonate was placed in a 250 mL three-necked flask, argon was introduced, and the mixture was reacted in an oil bath at 190° C. for 2 h. The mixture was cooled, taken out and ground to obtain orange-red zirconium polyacetylacetonate powder.
[0089] 2) 4 g of polycarbosilane powder and the polyacetylacetonate zirconium powder obtained in step 1) were mixed and added with 40 mL of xylene and then ultrasonically dispersed for 30 min to obtain an orange-red solution. The solution was then poured into a two-necked flask, a distillation device and a reflux device were set up, and argon gas was passed through. After reacting at 150° C. for 3 h, the temperature was raised to 160° C. to evaporate the xylene, and cross-linked at 300° C. for 3 h to obtain an orange solid, which was ground to obtain an orange powder.
[0090] 3) Take 2g of the orange powder prepared in step 2) and add it to 40mL of xylene to dissolve to obtain an orange solution, and then add 0.05mL of Custer platinum catalyst. Add 0.02g of GO powder to 40mL of distilled water and disperse it evenly by ultrasonication, then add 2mL of vinyltriethoxysilane, and adjust the pH of the solution to below 2 with dilute hydrochloric acid. Mix the above two solutions in a beaker, stir the reaction in a water bath at 60℃ for 30min, and then let it stand for 30min. Take the upper brown-gray organic layer, rotary evaporate it under vacuum at 70℃ for 40min, and grind it to obtain a gray-brown precursor powder.
[0091] 4) Add 2g of polycarbosilane powder to 40mL of xylene to dissolve to obtain a transparent colorless solution, and then add 0.05mL of Custer platinum catalyst to obtain a golden solution. Add 0.02g of GO powder to 40mL of distilled water, ultrasonically disperse it evenly, then add 2mL of vinyltriethoxysilane, and adjust the pH of the solution to below 2 with dilute hydrochloric acid. Mix the above two solutions in a beaker, stir magnetically in a 60℃ water bath to react for 30min. After the reaction is completed, take out the beaker and let it stand for 30min. Take the upper gray organic layer and rotary evaporate it under vacuum at 70℃ for 40min, then grind it to obtain a gray solid powder PVG.
[0092] 5) 4.32 g of zirconium acetylacetonate was placed in a 250 mL three-necked flask, argon was introduced, and the mixture was reacted in an oil bath at 190° C. for 2 h. The mixture was cooled, taken out and ground to obtain orange-red zirconium polyacetylacetonate powder.
[0093] 6) 4 g of the PVG powder described in step 4) and the polyacetylacetonate zirconium powder described in step 5) were mixed and added to 40 mL of xylene and then ultrasonically dispersed for 30 min to obtain a reddish brown turbid liquid. Then the mixture was poured into a two-necked flask, a distillation device and a reflux device were set up, and argon gas was passed through. After reacting at 150° C. for 3 h, the temperature was raised to 160° C. to evaporate the xylene, and then reacted at 300° C. for 3 h and ground to obtain a brown solid powder of a ceramic filler precursor.
[0094] 7) The brown solid powder obtained in step 6) was placed in an alumina crucible and heated in an argon atmosphere (flow rate 60 mL min -1 ) was pyrolyzed at 1300℃ in a tube furnace (heating rate 4℃·min -1 ), keep warm for 30 minutes and then cool with the furnace to obtain black self-generated ultra-high temperature ceramic reinforced SiC ceramic filler powder.
[0095] 8) The gray-brown precursor powder obtained in step 3), the self-generated ultra-high temperature ceramic reinforced SiC ceramic filler powder obtained in step 7) and the boron powder are uniformly mixed in a planetary ball mill at a mass ratio of 100:100:6.2. The ball milling adopts a positive and negative rotation alternating mode, and the rotation direction is changed every 1 hour. The mass ratio of the abrasive and the grinding ball is 1:4, the medium is anhydrous ethanol, the rotation speed is 400 rpm, and the ball milling time is 18 hours. After ball milling, the abrasive is fully dried to obtain a black mixed powder.
[0096] 9) 0.5 g of the black mixed powder obtained in step 8) was poured into a 16 mm diameter round stainless steel mold, and the mold was demolded after maintaining the pressure at 200 MPa on a hydraulic press for 20 seconds to obtain a ceramic green body.
[0097] 10) The ceramic green body obtained in step 9) was placed in a tube furnace under the protection of argon atmosphere (flow rate 60 mL min -1 ) and then sintered again at 1300℃ (heating rate 4℃·min -1 ), keep warm for 30 minutes and then cool with the furnace to obtain a black self-generated ultra-high temperature ceramic reinforced silicon carbide composite material.
[0098] Basic physical parameters: The ceramic yield of silicon carbide composite material is 88.25-89.25%, the linear shrinkage is 8.38-9.50%, and the density is 1.75-1.85 g / cm 3 , the open pore volume fraction is 24.27~31.50%.
[0099] Mechanical properties test: The hardness of the silicon carbide composite material is 9.95-11.32GPa, and the fracture toughness is 4.11-4.70MPa·m 1 / 2 The bending strength is 94.564~115.49MPa, and the compressive strength is 269.52~323.57MPa.
[0100] Example 7
[0101] 1) 2.16 g of zirconium acetylacetonate was placed in a 250 mL three-necked flask, argon was introduced, and the mixture was reacted in an oil bath at 190° C. for 2 h. The mixture was cooled, taken out and ground to obtain orange-red zirconium polyacetylacetonate powder.
[0102] 2) 4 g of polycarbosilane powder and the polyacetylacetonate zirconium powder obtained in step 1) were mixed and added with 40 mL of xylene and then ultrasonically dispersed for 30 min to obtain an orange-red solution. The solution was then poured into a two-necked flask, a distillation device and a reflux device were set up, and argon gas was passed through. After reacting at 150° C. for 3 h, the temperature was raised to 160° C. to evaporate the xylene, and cross-linked at 300° C. for 3 h to obtain an orange solid, which was ground to obtain an orange powder.
[0103] 3) Take 2g of the orange powder prepared in step 2) and add it to 40mL of xylene to dissolve to obtain an orange solution, and then add 0.05mL of Custer platinum catalyst. Add 0.02g of GO powder to 40mL of distilled water and disperse it evenly by ultrasonication, then add 2mL of vinyltriethoxysilane, and adjust the pH of the solution to below 2 with dilute hydrochloric acid. Mix the above two solutions in a beaker, stir the reaction in a water bath at 60℃ for 30min, and then let it stand for 30min. Take the upper brown-gray organic layer, rotary evaporate it under vacuum at 70℃ for 40min, and grind it to obtain a gray-brown precursor powder.
[0104] 4) Add 2g of polycarbosilane powder to 40mL of xylene to dissolve to obtain a transparent colorless solution, and then add 0.05mL of Custer platinum catalyst to obtain a golden solution. Add 0.02g of GO powder to 40mL of distilled water, ultrasonically disperse it evenly, then add 2mL of vinyltriethoxysilane, and adjust the pH of the solution to below 2 with dilute hydrochloric acid. Mix the above two solutions in a beaker, stir magnetically in a 60℃ water bath to react for 30min. After the reaction is completed, take out the beaker and let it stand for 30min. Take the upper gray organic layer and rotary evaporate it under vacuum at 70℃ for 40min, then grind it to obtain a gray solid powder PVG.
[0105] 5) 4.32 g of zirconium acetylacetonate was placed in a 250 mL three-necked flask, argon was introduced, and the mixture was reacted in an oil bath at 190° C. for 2 h. The mixture was cooled, taken out and ground to obtain orange-red zirconium polyacetylacetonate powder.
[0106] 6) 4 g of the PVG powder described in step 4) and the polyacetylacetonate zirconium powder described in step 5) were mixed and added to 40 mL of xylene and then ultrasonically dispersed for 30 min to obtain a reddish brown turbid liquid. Then the mixture was poured into a two-necked flask, a distillation device and a reflux device were set up, and argon gas was passed through. After reacting at 150° C. for 3 h, the temperature was raised to 160° C. to evaporate the xylene, and then reacted at 300° C. for 3 h and ground to obtain a brown solid powder of a ceramic filler precursor.
[0107] 7) The brown solid powder obtained in step 6) was placed in an alumina crucible and heated in an argon atmosphere (flow rate 60 mL min -1 ) was pyrolyzed at 1300℃ in a tube furnace (heating rate 4℃·min -1 ), keep warm for 30 minutes and then cool with the furnace to obtain black self-generated ultra-high temperature ceramic reinforced SiC ceramic filler powder.
[0108] 8) The gray-brown precursor powder obtained in step 3), the self-generated ultra-high temperature ceramic reinforced SiC ceramic filler powder obtained in step 7) and the boron powder are uniformly mixed in a planetary ball mill at a mass ratio of 100:100:22.2. The ball milling adopts a positive and negative rotation alternating mode, and the rotation direction is changed every 1 hour. The mass ratio of the abrasive and the grinding ball is 1:4, the medium is anhydrous ethanol, the rotation speed is 400 rpm, and the ball milling time is 18 hours. After ball milling, the abrasive is fully dried to obtain a black mixed powder.
[0109] 9) 0.5 g of the black mixed powder obtained in step 8) was poured into a 16 mm diameter round stainless steel mold, and the mold was demolded after maintaining the pressure at 200 MPa on a hydraulic press for 20 seconds to obtain a ceramic green body.
[0110] 10) The ceramic green body obtained in step 9) was placed in a tube furnace under the protection of argon atmosphere (flow rate 60 mL min -1 ) and then sintered again at 1300℃ (heating rate 4℃·min -1 ), keep warm for 30 minutes and then cool with the furnace to obtain a black self-generated ultra-high temperature ceramic reinforced silicon carbide composite material.
[0111] Basic physical parameters: The ceramic yield of silicon carbide composite material is 87.45-88.13%, the linear shrinkage is 7.80-8.20%, and the density is 1.63-1.74 g / cm 3 , the open pore volume fraction is 28.92~39.37%.
[0112] Mechanical properties test: The hardness of the silicon carbide composite material is 3.41-4.50 GPa, and the fracture toughness is 2.59-3.31 MPa·m 1 / 2 The bending strength is 64.82~73.85MPa, and the compressive strength is 180.40~212.78MPa.
[0113] The self-generated ultrahigh temperature ceramic reinforced silicon carbide composite material of the present invention is black, has good integrity, low density, excellent mechanical properties, a dense and smooth surface, and no cracks or holes visible to the naked eye. The ultrahigh temperature phase has good compatibility with SiC ceramics.
[0114] The in-situ ultra-high temperature ceramic reinforced silicon carbide composite material of the present invention has an X-ray diffraction pattern ( Figure 1 ) has the following characteristics: there are diffraction peaks at 2θ = 35.6° / 60.2° / 71.7° attributable to the (111) / (220) / (311) crystal planes of β-SiC, and at 2θ = 30.2° / 50.2° attributable to t-ZrO 2 The (101) / (112) crystal plane diffraction peak at 2θ=41.6° is attributed to ZrB 2The (101) crystal plane diffraction peak at 2θ = 44.4° is attributed to TiB 2 The difference between Example 4 and Example 5 is whether boron powder is introduced during ball milling. The addition of boron powder can generate B 2 O 3 and B 4 C, is conducive to removing oxygen and free carbon in the system, B 2 O 3 Part of the volatilization takes away the oxygen, while the molten B 2 O 3 It can improve the density of the sample and further improve the mechanical properties. In addition, boron thermal reaction will occur in the system, and t-ZrO 2 Phase reacts with boron powder to generate ultra-high temperature ZrB 2 phase, can improve the thermal shock resistance of SiC composite materials. 2 The diffraction peak intensity is weaker than that of Example 4, and ZrB 2 Characteristic peak.
[0115] The polymer precursor powders in Examples 1 to 3 of the present invention have an infrared spectrum ( Figure 2 ) has the following characteristics: Si-C (830cm -1 ),Si-CH 2 -Si(1020cm -1 )、Zr-OC(1033cm -1 )、Zr-O-Si(980cm -1 )、Si-OC(1100cm -1 )、C=C(1600cm -1 )、Si-H(2100cm -1 ),-CH 2 -(1410cm -1 ),Si-CH 3 (1250cm -1 、2950cm -1 ) and other structures, the Si-H peak intensity is compared with the internal standard Si-CH 3 The peak intensity gradually decreases with the increase of Zr content, indicating the successful reaction of Si-H bonds and ultrahigh temperature metal oligomers.
[0116] The PVG of the present invention and the three ceramic filler precursors of Examples 3 to 7 are brown solid powders (in Figure 3 In the infrared spectrum of the precursor powder of zirconium polyacetylacetonate ( Figure 3 ) has the following characteristics: Si-C (830cm -1),Si-CH 2 -Si(1020cm -1 )、Zr-OC(1033cm -1 )、Zr-O-Si(980cm -1 )、Si-OC(1100cm -1 ), =CH 2 (1450cm -1 )、C=C(1600cm -1 )、Si-H(2100cm -1 ),-CH 2 -(1410cm -1 ),Si-CH 3 (1250cm -1 、2950cm -1 ) and other structures, the Si-H peak intensity is compared with the internal standard Si-CH 3 The peak intensity gradually decreases with the increase of Zr content, and the characteristic signal of ultrahigh temperature metal oligomers gradually increases, indicating the successful reaction of Si-H bonds in PVG and ultrahigh temperature metal bonds, and the successful cross-linking of ultrahigh temperature metal oligomers and PVG.
[0117] Surface scanning electron microscope image of the in-situ ultrahigh temperature ceramic reinforced silicon carbide composite material according to Example 1 of the present invention ( Figure 4 ) has the following characteristics: the ceramic surface is flat, dense and crack-free, the in-situ self-generated ultra-high temperature ceramic phase is evenly distributed, integrated with the SiC ceramic matrix, and tightly bonded.
[0118] Surface scanning electron microscope image of the in-situ ultrahigh temperature ceramic reinforced silicon carbide composite material according to Example 6 of the present invention ( Figure 5 ) has the following characteristics: the ceramic surface is flat, dense and crack-free, the in-situ self-generated ultra-high temperature ceramic phase is evenly distributed, and the zirconium boride microcrystals are embedded in the SiC ceramic matrix, which is tightly combined and can effectively strengthen the ceramic.
[0119] In the present invention, the ultra-high temperature metal oligomer is obtained by polymerizing acetylacetone refractory metal salt, and most of the acetylacetone groups are removed in advance to avoid introducing too much oxygen to affect the high temperature resistance of the ceramic. The oligomer retains the molecular solubility and reaction sites, and the equal unit Si-H bonds can simultaneously access multiple metal atoms, solving the problem of the small amount of introduction when the acetylacetone ultra-high temperature metal chelate reacts with polycarbosilane. In addition, the polymer precursor PVG structure is a comb-shaped branched structure formed by polycarbosilane grafted graphene, which can avoid the polycarbosilane from entangled to form a mesh structure when cross-linking with the acetylacetone refractory metal salt, avoid the generation of steric hindrance, and increase the Si-H bond reaction rate and the ultra-high temperature metal content in the ceramic. Self-generated ultra-high temperature ceramic reinforced silicon carbide composite materials contain Si, C, O and ultra-high temperature metal elements such as Ti, Zr, Hf, etc. The introduction of ultra-high temperature metal elements through the precursor method can achieve atomic level uniformity. In the obtained composite material, the in-situ self-generated ultra-high temperature ceramics are uniformly distributed in the SiOxCy amorphous phase, and β-SiC nanocrystals and ultra-high temperature phases are uniformly embedded in the amorphous ceramic network, which can enhance the mechanical properties and high temperature resistance and oxidation resistance of SiC composite ceramics.
[0120] The above embodiments are only preferred embodiments of the present invention and cannot be considered to limit the scope of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the present invention.
Claims
1. A method for preparing an in-situ ultra-high temperature ceramic reinforced silicon carbide composite material, characterized in that: The following steps are involved: 1) dissolving polycarbosilane powder and ultra-high temperature metal oligomer powder in an organic solvent, and then placing under a protective atmosphere, subjecting to high temperature reflux, distillation and high temperature crosslinking to obtain a solid, grinding to obtain a powder, dissolving the powder in an organic solvent to obtain a modified polycarbosilane solution, and dropping a platinum catalyst; adding a silane coupling agent to a graphene oxide dispersion, mixing the mixture into the modified polycarbosilane solution to which the platinum catalyst has been dropped, heating and stirring to react, rotary evaporating and grinding to obtain a SiC ceramic precursor powder; 2) Mixing PVG powder and ultra-high temperature metal oligomer powder in an organic solvent, and then placing it under a protective atmosphere, undergoing high temperature reflux, distillation, and high temperature cross-linking, and then cooling it out, grinding it, and finally high temperature cracking it to obtain SiC ceramic filler powder; 3) ball-milling the SiC ceramic precursor powder prepared in step 1), the SiC ceramic filler powder prepared in step 2) and the boron powder, pressing the tablets, demolding to obtain a ceramic green body, and then sintering at high temperature under protective atmosphere to obtain a self-generated ultra-high temperature ceramic reinforced silicon carbide composite material.
2. The method for preparing an in-situ ultra-high temperature ceramic reinforced silicon carbide composite material according to claim 1, characterized in that: In step 1) and step 2), the preparation method of the ultra-high temperature metal oligomer powder is to subject one or more of diisopropyl di(acetylacetonate) titanate, acetylacetonoxy titanium, acetylacetonate zirconium, acetylacetonate hafnium, acetylacetonate aluminum, acetylacetonate tantalum, acetylacetonate yttrium, acetylacetonate chromium, and acetylacetonate nickel to self-polymerization in a constant temperature oil bath at 160 to 200°C for 0.5 to 3 hours to obtain the powder.
3. The method for preparing an in-situ ultra-high temperature ceramic reinforced silicon carbide composite material according to claim 1, characterized in that: In step 1) and step 2), the organic solvent is xylene, and the protective atmosphere is one of argon and nitrogen.
4. The method for preparing an in-situ ultra-high temperature ceramic reinforced silicon carbide composite material according to claim 1, characterized in that: In step 1), the mass ratio of polycarbosilane powder to ultra-high temperature metal oligomer powder is 100:(5-100), the reaction conditions are reflux at 140-160°C for 2-6 hours, then heating to distill the solvent, and cross-linking reaction at 290-310°C for 2-4 hours; the concentration of the modified polycarbosilane solution is 0.01-0.1 g / mL, and the heating and stirring is 50-70°C at a speed of 5-20 rpm for 20-60 minutes.
5. The method for preparing an in-situ ultra-high temperature ceramic reinforced silicon carbide composite material according to claim 1, characterized in that: In step 2), the mass ratio of PVG powder to ultrahigh temperature metal oligomer powder is 100:(10-200), the reaction conditions are reflux at 140-160° C. for 2-6 hours, then heating to distill the solvent, and cross-linking reaction at 290-310° C. for 2-4 hours.
6. The method for preparing an in-situ ultra-high temperature ceramic reinforced silicon carbide composite material according to claim 1, characterized in that: In step 2), the high temperature pyrolysis is carried out under the protection of argon atmosphere at 3-10°C·min -1 The temperature is raised to 900-1500°C at a heating rate and kept at this temperature for 1-60 minutes.
7. The method for preparing an in-situ ultra-high temperature ceramic reinforced silicon carbide composite material according to claim 1, characterized in that: In step 3), the mass ratio of SiC ceramic precursor powder, SiC ceramic filler powder and boron powder is 100:(0-200):(0-23).
8. The method for preparing an in-situ ultra-high temperature ceramic reinforced silicon carbide composite material according to claim 1, characterized in that: In step 3), the ball milling time is 9 to 20 hours, the rotation speed is 300 to 400 rpm; the tableting pressure is 90 to 300 MPa, and the holding time is 15 to 30 seconds.
9. The method for preparing an in-situ ultrahigh temperature ceramic reinforced silicon carbide composite material according to claim 1, characterized in that: In step 3), the high temperature sintering is carried out under the protection of argon atmosphere at 3-10°C·min -1 The temperature is raised to 900-1500°C at a heating rate and kept at this temperature for 1-60 minutes.
10. An in-situ ultra-high temperature ceramic reinforced silicon carbide composite material, characterized in that: Prepared by the preparation method described in claims 1 to 9.
Citation Information
Patent Citations
Method and equipment for preparing precursor body of poly carbon silane ceramics containing zirconium
CN100486930C
A method for preparing zirconium-containing ceramic precursors
CN107805307B
SiC fiber containing nano ZrB2-Hf as well as preparation method and application thereof
CN110395987A
Bulk silicon carbide polymer precursor ceramic and blending-cracking preparation method thereof
CN110467467A
Novel method for preparing zirconium-containing polycarbosilane
CN115716917A